Transcendental leadership and organizational citizenship behavior: Investigating the role of spirituality in the workplace - Iman Fatollah Najarbashi; Ali Aalikhani (Management Science Letters)
This paper studies the relationship between transcendental leadership and organizational citizenship behavior by investigating the role of spirituality in the workplace as a mediator. The study is executed for a case study of an Iranian insurance firm located in city of Tehran, Iran. The survey uses three questionnaires for transcendental leadership, spirituality in the workplace and organizational citizenship behavior. The results indicate that there were some meaningful relationships between the components of transcendental leadership and organizational citizenship behavior and element of spirituality in the workplace and organizational citizenship behavior. In addition, the study indicates that there were positive and meaningful relationships between vision/hope/faith and spiritual traditions, between components of transcendental and spiritual rituals, between oriented leadership and ultimately transcendent and spiritual components of oriented leadership. However, the study does not find any relationship between the two components of love, friendship and leaders’ spiritual growth and its subordinates and variable of oriented tradition of spirituality.